ANALISIS MAKNA SIMBOLIK DALAM PAKAIAN ADAT DAN ASESORIS SUKU ABUIDI DESA LEMBUR BARAT KABUPATEN ALOR - Vera M. Kabey; Vani E. Maninyeni, Yolanda Laumai, Yosin Djolelang, Yesgelode Lauata, Welmince Onbila, Halena Muna B (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The purpose of this study examines the Symbolic Meaning in the Customary Clothing and Accessories of the Abui Tribe in West Lembur Village, Alor Regency, The research method used is a qualitative approach with observation techniques, in-depth interviews, and literature studies. The results showed that the motifs in the Abui Tribe's woven fabric reflect the community's relationship with nature, ancestors, and traditional values that are upheld. Certain colours in traditional clothing have symbolic meanings related to courage, purity, and wisdom. In addition, accessories such as headbands, beaded necklaces, and metal bracelets have functions not only as decoration, but also as spiritual protection and group identity.Based on the results of the research, it can be concluded that this research confirms that the Abui's traditional clothing and accessories are not just cultural products, but also symbolic means of communication that reflect their belief system and social structure. By understanding this symbolic meaning, it is hoped that the cultural heritage of the Abui Tribe can continue to be preserved and appreciated as part of the cultural wealth in Indonesia.